Earth Observation (EO), Remote Sensing (RS), and Geoinformation (GI) Applications in Svalbard (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Earth observation (EO), remote sensing (RS), and geoinformation (GI) technologies play a critical role in the study of Svalbard's environment, providing insights into the region's changes and supporting decision-making processes. This reprint presents a comprehensive overview of the applications of EO and RS technologies in Svalbard, covering a wide range of topics related to the environment. It includes contributions from leading experts in the field, providing insights into the current state of the art and future directions for research. The reprint starts by introducing the status of EO and RS in Svalbard, providing a solid foundation for readers new to the field. It then delves into specific applications of these technologies, including the monitoring of glaciers, snow cover, and permafrost using ground-, space-, and air-based RS platforms. Overall, this book aims to provide a comprehensive overview of the applications of EO and RS technologies in Svalbard, highlighting their importance in understanding and addressing the challenges faced by the region. It will be a valuable resource for researchers, students, policymakers, and practitioners in the fields of environmental science, geography, and remote sensing.